Empiric antibiotic regimens for neonatal sepsis in Australian and New Zealand neonatal intensive care units. (19th April 2017) - Carr, Jeremy P; Burgner, David P; Hardikar, Rohan S; Buttery, Jim P
Abstract : Aim: Neonatal sepsis remains an important cause of morbidity and mortality, and requires prompt empiric treatment. However, only a minority of babies who receive antibiotics for suspected sepsis have an infection. Antimicrobial exposure in infancy has important short‐ and long‐term consequences. There is no consensus regarding empirical antimicrobial regimens. Methods: The study included a survey of empiric antimicrobial regimens in all tertiary neonatal intensive care units in Australia and New Zealand in 2013–2014. Results: All 27 units responded. For early‐onset sepsis, all units used a combination of gentamicin with either penicillin or ampicillin. For late‐onset sepsis, the frequency of units using empiric vancomycin (41%) versus empiric flucloxacillin (48%) was similar. Gestational age or the presence of a central venous catheter had little influence on using vancomycin instead of flucloxacillin. For late‐onset sepsis with meningitis there was marked variation in antimicrobial combinations, with 15 different regimens described. A total of 93% used a cefotaxime‐based regimen, either as monotherapy (22%) or combined with a second (22%) or third (48%) agent. For suspected necrotising enterocolitis, 89% used an aminoglycoside, metronidazole and a penicillin. Historical outbreaks of multi‐resistant organisms exerted long‐term influence over regimen choice. Conclusions: There was limited use of broad‐spectrum agents such as carbapenems or third‐generation cephalosporins. In this region with low methicillin‐resistant Staphylococcus aureus prevalence, empiric vancomycin use was common, selected for activity against coagulase‐negative staphylococci. Empiric vancomycin is rarely necessary because coagulase‐negative staphylococci are often contaminants and sepsis is rarely fulminant, occurring almost exclusively in extremely low birthweight infants. Implementation of appropriate, local antimicrobial policies is crucial to minimise antimicrobial exposure in this vulnerable population and halt the development of antimicrobial resistance.